Impacts of COVID-19 pandemic on global research - Xu, X (DUZ Academic Publishers, 2020)
The COVID-19 pandemic is transforming the academic world. International collaboration and competition continue through the crisis. The global research community is showing openness, resilience, and humanism. The forced immobility of researchers raises both challenges and opportunities for change. Inequality, ethical concerns, and questions on research impacts are intensified by the pandemic. A reflection on current changes helps to reimagine and rebuild future global research.